Laparoscopic Versus Open Surgery for Acute Appendicitis - Kamiya, Satoshi; Sumida, Wataru; Suzuki, Hideaki; Sato, Taichi; Asaba, Yuutarou; Kubota, Hitoshi (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2003)
Acute appendicitis is now commonly treated by laparoscopic appendectomy. Patients who underwent operations for acute appendicitis performed in our hospital over the past three years were divided into a laparoscopic group and and an open-surgery group and compared with respect to the following parameters: sex, age, postoperative start, of oral feeding frequency of painkiller use, operation time, incidence of complications, total cost, and length of hospital stay. The results showed a longer operation time, lower incidence of complications, higher cost, and shorter hospital stay in the laparoscopic group than in the open-surgery group. The subjects were also classified into a mild disease group and a severe disease group and compared in terms of the same parameters. The advantage of laparoscopic appendectomy was highly evident in the severe disease group, but in the mild disease group the incidence of complications in the laparoscopic surgery group was to the incidence in the open surgery group. These results suggest that laparoscopic appendectomy may become the first choice of treatment for acute appendicitis.